Employee retention at ‘Precious’ English language course in Surabaya - Eddy Roesdiono; Pinky Saptandari EP; Dewi Retno Suminar (Faculty of Social and Political Science, Universitas Airlangga, 2019)
Employee retention is related to the ways in which an organization keeps its employees. Failure to maintain employee retention may lead to unfavorable issues that negatively affect an organization’s performance. As a medium-sized organization, the Precious English Language training institution presents a unique state of employee retention in employing a balanced number of full-time and part-time teachers, most of whom have served at the institution between 10 and 29 years. The research on employee retention at Precious was conducted qualitatively and studied teachers who had served over ten years. The study also used other related artefacts to support findings. Semi-structured interviews were also conducted alongside observation of the teachers. The research results suggest that employee retention at Precious has been a natural result of the physically and emotionally favorable work environment that has arisen from the institution’s effort to maintain excellent teaching methods and persistent organization culture. Such job satisfaction has led to open employee engagement which has further contributed to the organization’s employee retention. The organization’s non-existence employee retention plan (that primarily uses non-financial rewards) has naturally led to increased employee retention alongside a drive to maintain the quality of the institution’s teaching in English Language.